2018
DOI: 10.1038/s41598-018-20589-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glyphosate, glufosinate, paraquat and paraquat-diquat on soil microbial activity and bacterial, archaeal and nematode diversity

Abstract: In this study, we investigated the effects of one-off applications of glyphosate, glufosinate, paraquat, and paraquat-diquat on soil microbial diversity and function. All herbicides were added to soil as pure compounds at recommended dose and were incubated under laboratory conditions for 60 days. High-throughput phylogenetic marker gene sequencing revealed that none of the herbicides significantly influenced the richness, evenness and composition of bacterial and archaeal communities. Likewise, the diversity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 59 publications
4
38
0
1
Order By: Relevance
“…The EC 50 values calculated for the genomic survey were also comparable to those observed in the functional tests. Similar results were reported for the metagenomic and functional impact on soil microorganisms of a Cu(OH) 2 nanopesticide [63] and four frequently used organic herbicides tested at a concentration corresponding to the upper recommended rate [64]. None of the herbicides affected the microbial richness or evenness, or the composition of the bacterial and archaeal communities, and from the functional perspective there was no significant effect on enzyme activities or the ability to degrade 15 substrates.…”
Section: Analysis Of Genomic Diversity By Ngssupporting
confidence: 80%
“…The EC 50 values calculated for the genomic survey were also comparable to those observed in the functional tests. Similar results were reported for the metagenomic and functional impact on soil microorganisms of a Cu(OH) 2 nanopesticide [63] and four frequently used organic herbicides tested at a concentration corresponding to the upper recommended rate [64]. None of the herbicides affected the microbial richness or evenness, or the composition of the bacterial and archaeal communities, and from the functional perspective there was no significant effect on enzyme activities or the ability to degrade 15 substrates.…”
Section: Analysis Of Genomic Diversity By Ngssupporting
confidence: 80%
“…Moreover, glyphosate residues have often been detected in soil and sediments (Peruzzo et al, 2008;Aparicio et al, 2013;Battaglin et al, 2014;MardianaJansar and Ismail, 2014), and it has been shown by numerous studies that glyphosate reaches surface waters via dispersed small soil particles or colloids (Struger et al, 2008;Slomberg et al, 2017). A recent study provides a Europe-wide assessment of the dispersal of glyphosate and AMPA in EU agricultural topsoils, being present in 45% of the topsoils collected, originating from 11 countries and six crop systems, with a maximum concentration of 2 mg/kg, as well as their potential spreading by wind and water erosion , further affected by small-scale sediment transport in water erosion (Bento et al, 2018), persisting under low bacterial activity in limited aerobic conditions or non-neutral pH (la Cecilia and Maggi, 2018), and adversely affecting soil microbial and nematodal diversity (Dennis et al, 2018). From the soil glyphosate can be translocated by plant roots; and it can affect non-target plants near agricultural ditches (Saunders and Pezeshki, 2015), and affect soil rhizosphere-associated bacterial communities (Newman et al, 2016) and soil Pseudomonas species (Aristilde et al, 2017).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…A recent study revealed that the exposure of honeybees to glyphosate alters the bee gut microbiota and increases the susceptibility to infection by opportunistic pathogens like Serratia marcescens (Motta et al, 2018). In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Thus, the effect of glyphosate on the bee microbiota seems to be unambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of glyphosate on the bee microbiota seems to be unambiguous. In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Moreover, the intensive use of the herbicide clearly stimulates the evolution of glyphosate-resistant plants and the use of genetically modified glyphosate-resistant crops decreases the diversity and abundance of wild plants (Heap, 2014;Schütte et al, 2017;Bagavathiannan and Davis, 2018).…”
Section: Introductionmentioning
confidence: 99%